Musculoskeletal model predicted paraspinal loading may quick estimate the effect of exercise on spine BMD - Liu, Shizhong; Xia, Xiaoyu; Nie, Yinxia; Huang, Mengen; Meng, Lin; Du, Juan (Frontiers in Bioengineering and Biotechnology, 2024)
PurposeSpine is the most commonly found fracture site due to osteoporosis. Combined exercise including high-impact and resistance exercise shows the potential to improve bone mineral density (BMD) in the spine. However, the mechanical loading introduced by exercise, which is the mechanism of BMD changes, has not been investigated. The purpose of this study is to provide a new insight to investigate the mechanical stimuli of exercise induced bone remodelling.MethodsTen postmenopausal women with osteopenia who finalized a 6-month combined exercise of high-impact and resistance intervention were included. The changes in BMD were analyzed based on QCT images obtained from pre and post intervention. A modified full-body musculoskeletal model was built to estimate paravertebral muscle force (MF) and intervertebral compression force (ICF) during daily activities (walking and heel drop) and combined exercise including high-impact (jumping) and resistance exercise (pulling elastic bands).ResultsThe paravertebral MF and ICF during jumping and pulling elastic bands exercise were all significantly greater than walking and heel drop exercise with up to 1.22–8.18 times. Spine BMD remained at the same level with no significant decline observed, especially at L1 (pre 247.95 ± 26.77 mg/cm3 and post 245.49 ± 22.04 mg/cm3). Comparing with daily activities, significant correlations were observed between the changes of BMD and the sum of spinal loadings generated by combined exercise at both global and segmental level (r = 0.687, p < 0.05).ConclusionIt has been proved that paravertebral muscle forces and intervertebral compression forces generated by the combined exercise, rather than daily exercise, were the main reasons for the improvement of spine BMD. This study contributes into the understanding of exercise induced spine adaptation as well as a potential in fast prediction to evaluate the effect of physical exercise therapy.